The risk of lymph node metastases and their impact on survival in patients with appendiceal neuroendocrine neoplasms: a systematic review and meta-analysis of adult and paediatric patients - Daskalakis, Kosmas (Endocrine, 2019)
BACKGROUND: There are no clear histopathological parameters determining the risk of lymph node (LN) metastases and appropriateness of completion prophylactic right hemicolectomy (RHC) in patients with appendiceal neuroendocrine neoplasms (ANENs). MATERIALS AND METHODS: The PubMed, Cochrane Library, Embase, Web of Science and SCOPUS databases were searched up to November 2018. Quality/risk of bias was assessed using the Newcastle–Ottawa Scale (NOS). RESULTS: A total of 526 articles were screened. In 11 adult and 3 paediatric studies, 602 and 77 unique patients, respectively, with ANEN and undergoing RHC, were included. The rate of LN metastases for a cutoff size >10 mm was 48.6% (vs 12.1% for lesions <10 mm) among adult patients, with an odds ratio (OR) of 4.8 (95% CI, 1.5–15.8). For 20 mm size cutoff, these figures were 61% (vs 28.2% for lesions <20 mm) with an OR of 3.2 (95% CI, 1.3–7.8). Vascular-, lymph vessel- and perineural invasions were identified as predictive factors for LN metastases in adult patients. In paediatric patients, there were no strong morphological predictors for LN metastases. The 10-year disease-specific survival (DSS) for adult patients without LN metastases was 99.2% vs 95.6% in patients with LN (OR: 0.2; 95% CI, 0.02–2.4). The complication rate of prophylactic RHC was 11.4%. CONCLUSIONS: This meta-analysis demonstrates that tumour size >20 mm as well as >10 mm and/or vascular-, lymph vessel- and perineural invasions are associated with increased risk for LN metastases in adult patients with ANEN. The prognostic value of LN positivity remains to be determined in further studies with long-term follow-up.